The Use of Codenames Game to Help Students in Learning Vocabulary - Octaviana, Inggil Tiara; Rahmah, Rayinda Eva; Puspitasari, Dewi (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2019)
English department students of IAIN Pekalongan have many shortcomings in memorizing vocabulary. This is evidenced by our observations when students are speaking in front of the class. Sometimes, students are confused about conveying information they want to deliver because they are constrained by a lack of memorization of vocabulary. The situation happens when students must use English in active discussions. So far, the students tend to memorize vocabulary. Besides that, vocabulary books are less effective and less interesting because it only relies on the use of language skills. One way to learn vocabulary in a simple way is through codenames game. This game provides many vocabularies that must be guessed by the players in a team. Then, another player should describe the word to be guessed. So, this research’s questions are how the codenames game is implemented due to learning English in a fun way. By reflecting the question, the purpose of this research is to provide information on the implementation of codenames game which helps English department students of IAIN Pekalongan enrich and build their vocabulary through a fun way using game cards. Based on our observation, the result showed that applying the codenames game could enrich the students’ vocabularies, be an alternative entertainer so that the students do not easily get bored, and strengthen the students’ memory. Thus, it can be concluded that playing codenames game promotes a helping way to enrich and build the students’ vocabulary.